FC001: Humoral Response to Third Dose of Sars-Cov-2 Vaccines in the CKD Spectrum: The Sencovac Study. (3rd May 2022) - Quiroga, Borja; Jose Soler Romeo, Maria; Ortiz, Alberto; De Sequera Ortiz, Patricia
Abstract: BACKGROUND AND AIMS: There is incomplete information on the impact of a third dose of the SARS-CoV-2 vaccine in advance chronic kidney disease (CKD). The aim of the present analysis was to evaluate the kinetics of humoral response in the CKD spectrum (KT, HD, PD and ND-CKD) 6 months after completing the initial vaccine schedule. Some patients of each group received a third dose before 6 months, providing a pragmatic insight into real-world responses to different vaccine schedules in patients with advanced CKD not on dialysis, on dialysis or in KT recipients. METHOD: The SENCOVAC study describes the humoral response and safety of different SARS-CoV-2 vaccines in a real-world setting in 3687 CKD patients: 787 kidney transplant (KT), 319 peritoneal dialysis (PD), 2297 haemodialysis (HD) and 284 non-dialysis-CKD (ND-CKD) patients. Anti-Spike antibodies were assessed in an efficacy analysis at 28 days ( n  = 1755), 3 months ( n  = 1386), and 6 months ( n  = 1018, of whom 628 had received a third vaccine dose). Adverse events (AEs) were registered during follow-up, including SARS-CoV-2 infections in the safety analysis. RESULTS: Among the patients included in the efficacy analysis, KT recipients presented lower anti-Spike antibody titers than other CKD cohorts at 28 days and 3 months (P < .001 for all). A total of 943 patients [249 (26%) KT, 108 (11%) PD, 511 (54%) HD and 75 (8%) ND-CKD] had negative baseline anti-Spike antibodies. Again, at 28 days or 3 months, KT recipients developed lower anti-Spike antibody titers than PD (P < .001), HD (P < .001) and ND-CKD (P< .001) patients. At 6 months, patients that had received a third vaccine dose had higher anti-Spike antibody titers than those without the third dose [1837 (507–9726) UI/mL versus 80 (19–409) ml/UI; P < .001] and this was evident in all CKD cohorts. Anti-Spike titers after the third dose were higher in patients boosted with mRNA-1273 than with BNT162b2 [1710 (322–9615) versus 472 (34–2094); P < .001). At 6 months, in patients that had received a third dose, a positive humoral response (anti-Spike antibodies > 36 UI/mL) was achieved in 584 (93%): 94 (80%) of 118 KT recipients, 20 (100%) of 20 patients on PD, 436 (96%) of 455 patients on HD and 34 (97%) of 35 patients with ND-CKD (Fig. 1 ). Among patients without humoral response 3 months after completing the initial vaccination schedule, 72 (69%) seroconverted after the third dose (62% KT, 76% HD, 100% ND-CKD, all PD patients had a positive humoral response at 3 months). Independent predictors of a positive humoral response at 6 months were not-KT (HR for KT 0.26, P = .011), third dose (HR 22.9, P < .001), initial mRNA-1273 (HT 1.78, P = .017) and humoral response at 3 months (HR 26.2, P < .001). Breakthrough SARS-CoV-2 infections occurred in 1.1% of patients, and mortality was 14.6%, none after the third dose. CONCLUSION: In the CKD spectrum, anti-Spike antibody titers continued to decrease from 3 to 6 months after complete vaccination, and KT recipients presented higher rates of negative humoral response at 6 months. A third dose of mRNA vaccine increased anti-Spike antibody titers but was still insufficient to spur a humoral immune response in at least 38% of KT recipients and 24% of patients on HD that lacked anti-SARS-CoV-2 antibodies 3 months post-initial vaccination. New strategies are urgently needed to protect CKD patients that remain negative for anti-SARS-CoV-2 antibodies, given the high mortality of breakthrough SARS-CoV-2 infections. GRAPHICAL ABSTRACT: